The Hadith Hermeneutics of Hasbi Ash-Shiddieqy and Its Implications for Islamic Law - Sohibul Haq; M. Inul Rizkiy (Yayasan Pesantren Mahasiswa An-Nur, 2025)
Contemporary Islamic jurisprudence faces the enduring challenge of reconciling the authority of the Prophetic tradition (Sunnah) with the evolving realities of the modern world. This article examines this problem through an analysis of the systematic hadith hermeneutics developed by the twentieth-century Indonesian scholar Tengku Muhammad Hasbi Ash-Shiddieqy. Using a qualitative hermeneutical approach, the study analyzes his principal works, Pokok-Pokok Ilmu Dirayah Hadis and Falsafah Hukum Islam, to reconstruct his framework for distinguishing between legislative (tashri‘) and non-legislative (ghayr tashri‘) hadith. The findings show that this distinction rests on the foundational premise of the Prophet’s dual capacities as a divine messenger (rasūl) and a human being (basyar). This conceptual division delineates a universally binding domain of law, primarily in matters of worship, from a non-binding sphere of worldly affairs in which human reason, empirical knowledge, and contextual understanding play a central role. The paradigmatic examples of the command to pray and the incident of date-palm pollination illustrate the practical application of this binary framework. The study concludes that Ash-Shiddieqy’s hermeneutical model constitutes a coherent and systematic methodology that integrates contextual reasoning within Islamic jurisprudence and serves as a principled framework for achieving the higher objectives of Islamic law (maqāṣid al-sharī‘ah).